Multiversal Utopias: The Jaqueira Reserve: Between Decolonial Resistance and the Community Economy in Building a Sustainable Future - Porsani, Juliana; S. Fortes, Bartira; de Camargo, Márcia F (Whispers from below: Community-based tourism and (other) Ecuadorian initiatives for alternative economies: A closer look, 2026)
This research examines the Reserva da Jaqueira as a real-world utopia and a space for decolonial resistance. Through a self-managed community economy, it subverts extractivist logic and the notion of modern progress. The study draws on concepts of the pluriverse and borderline thinking to demonstrate how cultural revitalization and territorial defense form a model of ancestral sustainability in the face of capitalism.